The Impact of The Covid-19 Pandemic on Local Development Management in Poland in The Aspect of Using Participatory Budgeting - Arkadiusz GRYKO; Michał OLEJNICZAK (Communications of International Proceedings, 2022)
The coronavirus pandemic has left its mark not only on the economy or interpersonal relations, but also on the functioning of local governments, which are the creators of local development. Forecast lower tax revenues due to the economic crisis, resulting from numerous restrictions on business activity, have forced many local governments in Poland to cut spending. In many local governments, the cuts also affected the operation of participatory budgetings, which are one of the tools of local development.
Keywords: Covid-19 pandemic; local development; management; participatory budgeting